The effect of the central bank liquidity support during pandemics: Evidence from the 1918 influenza pandemic - Haelim Park Anderson; Jin Wook Chang; Adam Copeland (Federal Reserve Bank of New York, 2020)
The coronavirus outbreak raises the question of how central bank liquidity support affects financial stability and promotes economic recovery. Using newly assembled data on cross-county flu mortality rates and state-charter bank balance sheets in New York State, we investigate the effects of the 1918 influenza pandemic on the banking system and the role of the Federal Reserve during the pandemic. We find that banks located in more severely affected areas experienced deposit withdrawals. Banks that were members of the Federal Reserve System were able to access central bank liquidity, enabling them to continue or even expand lending. Banks that were not System members, however, did not borrow on the interbank market, but rather curtailed lending, suggesting that there was little-to-no pass-through of central bank liquidity. Further, in the counties most affected by the 1918 pandemic, even banks with direct access to the discount window did not borrow enough to offset large deposit withdrawals and so liquidated assets, suggesting limits to the effectiveness of liquidity provision by the Federal Reserve. Finally, we show that the pandemic caused only a short-term disruption in the financial sector.
Keywords: E32; G21; N22; 330; 1918 influenza; pandemics; financial stability; bank lending; economic recovery